Ratios of Four STAT3 Splice Variants in Human Eosinophils and Diffuse Large B Cell Lymphoma Cells - Turton, Keren B.; Annis, Douglas S.; Rui, Lixin; Esnault, Stephane; Mosher, Deane F. (PloS one, 2015)
Signal transducer and activator of transcription 3 (STAT3) is a key mediator of leukocyte differentiation and proliferation. The 3' end of STAT3 transcripts is subject to two alternative splicing events. One results in either full-length STAT3α or in STAT3β, which lacks part of the C-terminal transactivation domain. The other is at a tandem donor (5') splice site and results in the codon for Ser-701 being included (S) or excluded (ΔS). Despite the proximity of Ser-701 to the site of activating phosphorylation at Tyr-705, ΔS/S splicing has barely been studied. Sequencing of cDNA from purified eosinophils revealed the presence of four transcripts (S-α, ΔS-α, S-β, and ΔS-β) rather than the three reported in publically available databases from which ΔS-β is missing. To gain insight into regulation of the two alternative splicing events, we developed a quantitative(q) PCR protocol to compare transcript ratios in eosinophils in which STAT3 is upregulated by cytokines, activated B cell diffuse large B cell Lymphoma (DLBCL) cells in which STAT3 is dysregulated, and in germinal center B cell-like DLBCL cells in which it is not. With the exception of one line of activated B cell DLCBL cells, the four variants were found in roughly the same ratios despite differences in total levels of STAT3 transcripts. S-α was the most abundant, followed by S-β. ΔS-α and ΔS-β together comprised 15.6 ± 4.0 % (mean ± SD, n = 21) of the total. The percentage of STAT3β variants that were ΔS was 1.5-fold greater than of STAT3α variants that were ΔS. Inspection of Illumina's "BodyMap" RNA-Seq database revealed that the ΔS variant accounts for 10-26 % of STAT3 transcripts across 16 human tissues, with less variation than three other genes with the identical tandem donor splice site sequence. Thus, it seems likely that all cells contain the S-α, ΔS-α, S-β, and ΔS-β variants of STAT3.